ASSESSMENT AND PROSPECTS OF USING CROWDSOURCING AS A TOOL OF EFFECTIVE PUBLIC ADMINISTRATION - Olga P. Sykovatova; Ludmila A. Chernobrodova (Статистика и экономика)
The article is devoted to the qualitative assessment of the possibilities of using different kinds of crowdsourcing in the field of state and municipal management. Systematized forms of sourcing, generalized types of crowdsourcing, disclosed fields of their application and realized projects. The conditions are investigated and limitations of using crowdsourcing in the state and municipal management.